CUSTOMER EXPERIENCE, SERVICE QUALITY DAN BRAND IMAGE YANG MEMPENGARUHI KEPUASAN PESERTA PELATIHAN BUSINESS WISDOM INSTITUTE (BWI) DI INDONESIA - Tin Agustina Karnawati; Armenia Widiastuti; Yunus Handoko (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2022)
Customer satisfaction is very important for the sustainability of a company. Whether or not consumers are satisfied with a company has an impact on the company. Likewise, the Business Wisdom Institute (BWI), which is a service provider company engaged in training, needs to maintain customer satisfaction in order to maintain the continuity of the company. This study aims to determine the effect of customer experience, service quality, and brand image on the satisfaction of the Business Wisdom Institute training participants. This type of research uses a quantitative approach and the method of analysis is multiple linear regression analysis. The subjects in this study were the participants of the Business Wisdom Institute training as many as 100 respondents and using a purposive sampling technique. The results of this study indicate that customer experience and brand image have a significant effect on the satisfaction of Business Wisdom Institute training participants, whereas service quality has no significant effect on the satisfaction of Business Wisdom Institute training participants.